Preclinical evaluation of collagen type I scaffolds, including gelatin-collagen microparticles and loaded with a hydroglycolic Calendula officinalis extract in a lagomorph model of full-thickness skin wound (2016)
Previously, we have developed collagen type I scaffolds including microparticles of gelatin-collagen type I (SGC) that are able to control the release of a hydroglycolic extract of the Calendula officinalis flower. The main goal of the present work was to carry out the preclinical evaluation of SGC alone or loaded with the C. officinalis extract (SGC-E) in a lagomorph model of full-thickness skin wound. A total of 39 rabbits were distributed in three groups, of 13 animals each. The first group was used to compare wound healing by secondary intention (control) with wound healing observed when wounds were grafted with SGC alone. Comparison of control wounds with wounds grafted with SGC-E was performed in the second group, and comparison of wounds grafted with SGC with wounds grafted with SGC-E was performed in the third group. Clinical follow-ups were carried in all animals after surgery, and histological and histomorphometric analyses were performed on tissues taken from the healed area and healthy surrounding tissue. Histological and histomorphometric results indicate that grafting of SGC alone favors wound healing and brings a better clinical outcome than grafting SGC-E. In vitro collagenase digestion data suggested that the association of the C. officinalis extract to SGC increased the SGC-E cross-linking, making it difficult to degrade and affecting its biocompatibility.